Mechanochemically Induced Chalcogenation of Bicyclic Arenes under Solvent‐, Ligand‐, Metal‐, and Oxidant‐Free Conditions. Issue 44 (27th November 2020) - Panja, Subir; Paul, Biprajit; Jalal, Swapnadeep; Ghosh, Tubai; Ranu, Brindaban C.
Abstract: A convenient method has been developed for the synthesis of biarenyl chalcogenides through the interaction of bicyclic arenes and diaryl dichalcogenides on the surface of basic alumina under ball milling without any metal catalyst or solvent. This methodology shows wide substrate scope and is of high potential in organic synthesis due to its green aspects of ease of operation, shorter reaction time, ambient conditions and high yields. Abstract : An efficient procedure for the mechanochemically induced oxidative chalcogenation of 2‐naphthol derivatives has been achieved under solvent and metal free condition.